Family stories - Salvador, Maita Songco; Aguirre, Aldy C. (Quezon City, Philippines Lampara Publishing House, Inc., 2024)
"Different families have different stories. And these different stories deserve to be heard. This book celebrates diversity while offering a glimpse of what binds families amidst differences."
Keywords: Children's stories, Philippine (English).; Family stories; Big books (Children's books).